ANALISA VARIASI KAMPUH DAN ARUS LISTRIK LAS PADA MATERIAL BAJA KARBON MENENGAH TERHADAP KEKUATAN TARIK DAN STRUKTUR MIKRO SAMBUNGAN LAS - Lasamahu, Stevanno B D; Huka, Graciadiana I; Nanulaitta, Nevada. JM (Jurusan Teknik Mesin, 2024)
This study aimed to investigate the effects of weld groove variations and welding current on the tensile strength and microstructure of medium carbon steel joints using FCAW (Flux-Cored Arc Welding). The researcher employed a quantitative approach with an experimental method. The specimens used in this research include FCAW with V-groove and 90 A current, FCAW with V-groove and 70 A current, FCAW with X-groove and 70 A current, FCAW with X-groove and 90 A current, raw material specimens, and microstructure specimens. The data analysis reveals that the highest average tensile stress value among the welded specimens was 463.50 MPa, observed in the FCAW X-groove with 90 A current specimen, while the FCAW V-groove with 70 A current specimen showed the lowest value at 295.1 MPa. Regarding the strain values, the FCAW X-groove with 90 A current specimen had the lowest average strain of 4.15%, whereas the FCAW V-groove with 70 A current specimen had the highest at 5.36%. In terms of microstructure, the FCAW V-groove with 70 A current specimen exhibited martensite, pearlite, and ferrite structures in the weld zone, and ferrite and pearlite structures in the heat-affected zone (HAZ) and base metal. For the FCAW X-groove with 90 A current specimen, pearlite and ferrite structures were found in the weld zone, HAZ, and base metal. Keywords: Carbon Steel, Weld Groove, Welding Current, Tensile Test, Microstructure